Honey locust (gleditsia triacanthos l. (fabaceae)) invasion effect on temperature, light and metabolism of a pampean stream (2014)
ABSTRACT The establishment of invader species in a region generally modifies the ecosystems where they are introduced. In this study we analyze the effect produced by a Gleditsia triacanthos (honey locust) invasion on a pampean stream. This organism modifies the temperature and the light reaching the stream. Thermal range shows significant differences between reaches but mean tem between 85 and 95 % down the trees. These modifications reduce the primary gross production of 2.7 to 1.7 g O2. m-2 at spring and of 25 to 20 g O2. m-2 at summer. Respiration in spring and summer is halved at invaded reaches, but net ecosystem metabolism is similar in both reach and seasons. Moreover, the reach invaded by honey locust show scarce macrophytes. We argue that the honey locust reduces the diversity by reduction of macrophytes and their associated organisms but also reduce the primary production causing changes in the food web. RESUMEN El asentamiento de especies invasoras en una región generalmente produce cambios en los ecosistemas en los que se introducen. En este caso se analiza el efecto producido por una invasión de Gleditsia triacanthos, la acacia negra, sobre un arroyo pampeano. Esta especie modifica el clima térmico y lumínico del tramo. La amplitud térmica se reduce significativamente en el tramo invadido aunque la temperatura promedio en ambos tramos es similar. La irradiación se reduce entre un 85 y un 95 % bajo el dosel arbóreo. Estas modificaciones disminuyen la producción primaria bruta de 2,7 a 1,7 g O2/m2 en primavera y de 25 a 20 g O2/m2 en verano. La respiración se reduce a la mitad en los tramos invadidos, tanto en primavera como en verano, siendo el metabolismo neto similar en ambos tramos y estaciones del año. Por otro lado, el tramo invadido por acacia tiene muy escasas macrófitas. Se postula que la invasión de acacias además de disminuir la biodiversidad por reducción de las macrófitas y de los organismos asociados a ella reduce la producción primaria provocando cambios en la red trófica.